Coherence Between the First and the Second Phase of Geography Teacher Training: A Qualitative Study on the Perspectives of Geography Teacher Trainers in Germany - Fischer, Frank (Journal of Geography Education, 2023)
Since the introduction of the internship semester in many German states in the last decade, findings on coherence in Geography teacher education have been rare. In the context of the present qualitative study, 23 Geography teacher trainers from twelve German states were interviewed. They have got an expert perspective on the progression between the first two phases of teacher education. The experts perceive various incoherencies between the phases, such as a distance between research and teacher training at universities and school practice. This might be due to a lack of cooperation between the teacher educators of the two phases. The teacher trainers name various approaches for improvement (e.g., professionalization of the internship semester).